2019
DOI: 10.1007/s00520-019-4652-4
|View full text |Cite
|
Sign up to set email alerts
|

Respectful encounters from healthcare professionals and return to work among 9032 long-term sick-listed due to cancer or due to other diagnoses: results from a Swedish population-based survey

Abstract: Purpose To examine whether experiences of positive respectful encounters and negative disrespectful encounters differ between sickness absentees with a cancer diagnosis and sickness absentees with other diagnoses, especially in relation to their ability to return to work (RTW). Methods A total of 9032 long-term sickness absentees in Sweden responded to a questionnaire (response rate 52%) about experiences of positive and negative encounters with healthcare professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Person‐centredness as an emerging approach for healthcare underlines the individual experiences of each patient in the forefront of care (2). The importance of feeling respected and being listened to in the clinical encounter has been highlighted in several studies (9, 11) and has been shown to be of significant importance, for example, for returning to work after a cancer diagnosis (19). Likewise, healthcare professionals highlight the importance to capture and interpret each patient's symptoms and perceived health (20) but also that the narrative‐based care involves great efforts (8, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Person‐centredness as an emerging approach for healthcare underlines the individual experiences of each patient in the forefront of care (2). The importance of feeling respected and being listened to in the clinical encounter has been highlighted in several studies (9, 11) and has been shown to be of significant importance, for example, for returning to work after a cancer diagnosis (19). Likewise, healthcare professionals highlight the importance to capture and interpret each patient's symptoms and perceived health (20) but also that the narrative‐based care involves great efforts (8, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the shortage of studies regarding experiences of encounters in healthcare of people suffering from fibromyalgia, we based an assumption from a population study in Sweden where 21% of the participants had negative experience of encounters in healthcare ( Månsson et al., 2019 ). We therefore estimated the frequency of negative experience to be 21%.…”
Section: Methodsmentioning
confidence: 99%